Introverted and Extroverted Personalites in Students’ English Acquisition Process: A Comparative Study - Isa, Isa; Permana, Dio Resta; Anggraini, Dita Rizki (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aimed at describing the differences between introverted and extroverted students in the process of acquiring English as a foreign language for class IX.7 students at SMP Negeri 56 Palembang. There were 30 students as the research samples, and the respondents in the research were 2 teachers who taught English in class IX. This research uses a qualitative descriptive method, data obtained using questionnaires, observation and interviews. The data in this study were analyzed using an in-depth observation method to identify differences in the English language acquisition process between introverted and extroverted studentsThe research results show that introverted students tend to be quieter or talk less but have long memories and show a deeper understanding of listening, observing and understanding. while extroverted students tend to develop speaking and interaction skills more quickly. In these differences, all students also have similarities, namely they have the same goal of acquiring and learning English and they also still need support and motivation from the teacher. This research also found that there are several obstacles or factors that influence student achievement; there is personality, attitude and motivation.